Correction of skeletal class 2 malocclusion with Carriere Motion appliance: case report - M. M. Shubitidze (Эндодонтия Today, 2022)
The article considers nonsurgical and nonextraction   method of treatment of patient with skeletal class 2 malocclusion.Aim. To evaluate the treatment effectiveness of Carrier Distalize, determing the short-term skeletal and dental effects occur as a result of Class II malocclusion correction utilizing the Carrière Overall, the Carriere Distalizer appears to be effective in early results in the treatment of Class II malocclusion.Materials and methods: A 25 years old  male patient presented for treatment exhibition a class 2 malocclusion with a severely  retrusive  mandible  was treated with Carrier motion  class 2 appliance , after previous  orthodontic unsuccessful treatment with extraction of the lower right premolar by brace system. the appliance was used for 5 month fool time. This systematic review was conducted and changes were analyzed from dental photo protocol, lateral cephalograms taken at the start and after and study model measurements from pre and post treatment Results:  the time of  skeletal class two correction in class one  for Carriere motion appliance was significantly shorter.   great mesial mandibular movement and improvement in sagittal skeletal relation were shown after carrier motion appliance treatment for five month.Conclusions. Treatment resulted that carrier motion appliance is simple to apply, comfortable for patient and affective in correcting class 2 malocclusion.